Burnout Syndrome in Caregivers of Patients with Childhood Disability - Arias, Walter (2019)
The aim of this study was to value the prevalence of burnout syndrome in caregivers of patients with disabilities from Arequipa City. The sample was conformed by 45 caregivers (91.42% female and 8.8% male) with and average age of 30.26 years old. We applied the Burnout Maslach Inventory, which has 22 items and three dimensions: exhaustion, cynicism and inefficacy. Its reliability is adequate for health personnel like this case (α= 0.721). The caregivers of patients with disability are women and relatives of the people who are under their responsibility. They also have high levels of exhaustion and inefficacy. Around 97.6% of people sampled have moderate levels of burnout syndrome. Moreover, women present major levels of cynicism than men, and while family caregivers have mayor levels of exhaustion, professional caregivers reach severe levels of inefficacy. We conclude that caregivers of people with disabilities have high risk of having burnout syndrome, which is characterized by severe levels of exhaustion and inefficacy.